Resolution of Deep Disagreement: Not Simply Consensus - Henderson, Leah (Informal Logic, 2020)
Robert Fogelin has argued that in deep disagreements, resolution cannot be achieved by rational argumentation. In response, Richard Feldman has claimed that deep disagreements can be resolved in a similar way to more everyday disagreements. I argue that Feldman’s claim is based on a relatively superficial notion of “resolution” of a disagreement whereas the notion at stake in Fogelin’s argument is more substantive. Furthermore, I argue that Feldman’s reply is based on a particular reading of Fogelin’s argument. There is an alternative reading, which takes the central concern to be the role of common ground in argumentation. Engaging with this version of Fogelin’s argument is also a worthwhile endeavour.